The Effectiveness of Audio-Visual Media and Flip Sheets on Cadres’ Knowledge, Attitude and Skills in Screening Children’s Growth and Development - Yani Suryani; Agus Riyanto; Novi Mauliku; Budiman; Dyan Kunthi (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
The problem of stunting in Indonesia is still a national concern, stunted children are at higher risk of developing degenerative diseases, such as cancer, diabetes, obesity and cognitive impairment. Analyzing the Effectiveness of Audio Visual Media and Flip Sheets in increasing the Knowledge, Attitudes and Skills of cadres in conducting child growth and development screening in the Cianjur Regency City Health Center area. Research design with a Quasi Experimental approach. The total sample size was 84, divided into 2 groups with a ratio of 1:1. The statistical analysis used is univariate, bivariate using the paired sample T test and Wilcoxon test, Multivariate using the multiple logistic regression test. The results showed significant difference in knowledge (p-value=0.001), attitude (p-value = 0,001) and skills (p-value = 0,001) before and after being given audiovisual media in the intervention group. And there is a significant difference in knowledge (p-value = 0.013); attitude (p-value = 0.026); and skills (p-value =0.001) in the intervention group and control group. The results of research using the multiple logistic regression test showed that there were confounding variables, namely age and education on attitudes and skills, while there were no confounding variables on knowledge. So it can be concluded that audiovisual media is effective in increasing the knowledge and skills of cadres. Therefore, audiovisual media can be used to increase cadres' knowledge and skills in screening children's growth and development.